2017
DOI: 10.3389/fphys.2017.00894
|View full text |Cite
|
Sign up to set email alerts
|

CXL-1020, a Novel Nitroxyl (HNO) Prodrug, Is More Effective than Milrinone in Models of Diastolic Dysfunction—A Cardiovascular Therapeutic: An Efficacy and Safety Study in the Rat

Abstract: The nitroxyl (HNO) prodrug, CXL-1020, induces vasorelaxation and improves cardiac function in canine models and patients with systolic heart failure (HF). HNO's unique mechanism of action may be applicable to a broader subset of cardiac patients. This study investigated the load-independent safety and efficacy of CXL-1020 in two rodent (rat) models of diastolic heart failure and explored potential drug interactions with common HF background therapies. In vivo left-ventricular hemodynamics/pressure-volume relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Earlier in vitro nuclear magnetic resonance studies (data not shown) demonstrated that BMS-986231 in phosphate-buffered saline was converted stoichiometrically to HNO and its inactive by-product, BMT-284730; furthermore, when this conversion in phosphate-buffered saline took place in the presence of excess glutathione, stoichiometric trapping of HNO as a glutathione adduct occurred. In addition, a study of CXL-1020 in rats reported hemodynamic effects that were not only similar to those seen with BMS-986231 in the present studies with dogs, but were different to those of the NO donor sodium nitroprusside (13) . Regarding the biochemical effects of BMS-986231 in humans, in the phase 2a study, BMS-986231 (3 to 12 μg/kg/min) was not associated with adverse changes in laboratory parameters, including brain natriuretic peptide, troponin I, serum creatinine, liver enzymes, hemoglobin, or platelet count (22) .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Earlier in vitro nuclear magnetic resonance studies (data not shown) demonstrated that BMS-986231 in phosphate-buffered saline was converted stoichiometrically to HNO and its inactive by-product, BMT-284730; furthermore, when this conversion in phosphate-buffered saline took place in the presence of excess glutathione, stoichiometric trapping of HNO as a glutathione adduct occurred. In addition, a study of CXL-1020 in rats reported hemodynamic effects that were not only similar to those seen with BMS-986231 in the present studies with dogs, but were different to those of the NO donor sodium nitroprusside (13) . Regarding the biochemical effects of BMS-986231 in humans, in the phase 2a study, BMS-986231 (3 to 12 μg/kg/min) was not associated with adverse changes in laboratory parameters, including brain natriuretic peptide, troponin I, serum creatinine, liver enzymes, hemoglobin, or platelet count (22) .…”
Section: Discussionsupporting
confidence: 72%
“…Nitroxyl (HNO) donors are a class of molecules with unique biochemical and pharmacological properties that have been investigated over several years for their potential therapeutic applications. Although related to nitric oxide (NO), the pharmacological effects of HNO are different from NO; these effects produce arterial and venous dilation, as well as direct, beneficial, cAMP/protein kinase A-independent lusitropic and inotropic effects, in both the normal and failing myocardium 8 , 10 , 12 , 13 . HNO enhances sarcoplasmic reticular calcium uptake and release through modulation of sarcoplasmic reticulum calcium 2+ adenosine triphosphatase (SERCA2a), phospholamban (PLN), and the ryanodine receptors.…”
mentioning
confidence: 99%
“…A 24G intravenous catheter was introduced through the jugular vein. In the first experiment, after the acquisition of echocardiographic images at baseline (BL), milrinone (MIL) (Maruishi Pharmaceutical, Osaka, Japan) was administered intravenously at a constant rate of 10 µL kg −1 min −1 according to the previously reported protocol [27]. Echocardiographic examinations were repeated 20 min after MIL infusion.…”
Section: Animal Preparation and Experimental Protocolmentioning
confidence: 99%
“…The latter has been attributed to general disulfide induction in oxidant-susceptible proteins that culminate in the enhancement of sarcomere shortening and cardiac myocyte relaxation. This includes an increase in Ca 2+ -reuptake into the SR and an acceleration of cross-bridge cycling by disulfide crosslinking of proteins localized to the SR—PLN and SERCA2a—and the myofilament—tropomyosin and the myosin light chains—compartment [ 204 , 205 , 206 , 207 , 208 ]. Recently, disulfide formation in PKA and PP2A subunits has been described to contribute to this scenario and to occur independently of β-adrenoceptor activation [ 44 ].…”
Section: Therapeutic Modulation Of Kinase/phosphatase Signalingmentioning
confidence: 99%